99.0k views
2 votes
1/2 (n – 4) – 7 = -2n+6

2 Answers

3 votes

Answer:

n=6 in this question i think

User Pedro Massango
by
5.8k points
0 votes

Answer:

n = 6

Explanation:

Simplify
(1)/(2) ·
(n-4)-7

n/2 -2 -7 =-2n +6

n/2 - 9+ -2n +6

Move all terms containing n to the left side of the equation.

n/2 - 9 +2n =6

To write 2

n as a fraction with a common denominator, multiply by

n/2 + 2n *(2/2) -9 = 6

combine 2n and (2/2)

n/2 + (2n*2)/2 -9 = 6

Combine the numerators over the common denominator.

(n+2n*2)/2 - 9 = 6

Simplify each term.

(n(1+2*2))/2 - 9 = 6

(n(1+4))/2 -9 = 6

(n*5)/ 2 - 9 = 6

5n/2 - 9 =6

Move all terms not containing n to the right side of the equation.

Add 9 to both sides of the equation.

5n/2 = 6 + 9

5n/2 = 15

Multiply both sides of the equation by 2/5

2/5 * 5n/2 = 2/5 *15

Simplify both sides of the equation.

2/5 * 5n/2

Cancel the common factor of 2

Cancel the common factor of 5

n = 2/5 *15

Cancel the common factor of 5

n = 2 * 3

Multiply

n = 6

.

User Ryan Tensmeyer
by
5.8k points